Comparative analysis of universal newborn hearing screening programs in Malaysia, China and Philippines - Abdul Majid, Abdul Halim; Ismail, Abdussalaam Iyanda; Zakaria, Mohd Normani; Abdullah, Nor Azimah Chew; Hamzah, Sulaiman; Mukari, Siti Zamratol-Mai Sarah (College of Law, Government and International Studies, Universiti Utara Malaysia, 2017)
Universal Newborn Hearing Screening Program (UNHS) has developed rapidly and tremendously in the world, but developing countries need contextual models for UNHS to optimize screening outcomes and costeffectiveness. Therefore, this study aims to document current UNHS practices in three developing countries; Malaysia, Philippines and China with the aim of comparing the reported practices to bring about some recommendations. Based on the comprehensive review of reports, published research, and other relevant materials, it is found that UHNS practices in the selected countries (Philippine, Malaysia, and China) have commonalities and differences. Newborn hearing screening is made binding on all caregivers in Philippine, whereas it is just recommended in Malaysia and China. Nevertheless, the protocols of UNHS program applied in the selected countries are similar. In the selected countries, the protocol involves OAE and AABR. Also, UNH has been well instituted in the selected countries, but certain challenges (e.g. poor follow-up) are debilitating the effectiveness of the screening in the selected countries, and the challenges should be well addressed and empirically studied. Furthermore, stakeholders could possibly benefit from the findings of this study and recognize the need to optimize the UNHS program through suggested factors. This study has hopefully contributed towards the enrichment of the relevant literature, and it could serve as a useful guide for stakeholders with regards to improvement of UNHS program in their respective countries.